Managing the moderation of school-based assessment at Grade 12 level in Gauteng - Grobler, Bennie; Loock, Coert; Govender, Prem (University of the Free State, 2013)
English: In 2000, the National Minister of Education mandated the inclusion of school-based assessment (SBA) as a component of the Senior Certificate (Grade 12) assessment. This study examines how managing the moderation of SBA could improve the quality of assessment at Grade 12 level. The literature study elucidates the underlying dimensions of managing SBA and the quantitative study investigates the perceptions of educators regarding these dimensions. The findings are consolidated into an enhanced model that calls for continuous moderation of assessment tasks at school level, based on the principles of systems theory.

Afrikaans: Die Minister van Onderwys het in 2000 die insluiting van skoolgebaseerde assessering (SGA) as integrale komponent van die Nasionale Senior Sertifikaat op Graad 12-vlak deur wetgewing verpligtend gemaak. Hierdie navorsingsprojek poog om aan te toon hoe die bestuur van moderering die kwaliteit van assessering op Graad 12-vlak kan verbeter. Die literatuurstudie het die onderliggende dimensies van SGA uitgeklaar en ondersoek deur van ’n kwantitatiewe navorsingsontwerp gebruik te maak ten einde onderwysers se persepsies aangaande die onderhawige assesseringsdimensies te bepaal. Die bevindinge is vervat in die ontwerp van ’n unieke assesseringsmodel, gebaseer op die fundamentele kenmerke van stelselteorie, wat die effektiwiteit van kwaliteitsversekering en moderering van kontinue-assesseringstake sal bevorder.
Keywords: School-based assessment; Grade 12